Accessory hepatic vein recanalization for hepatic vein-type Budd–Chiari syndrome. Issue 4 (2nd August 2021) - Li, Dong-Mei; Yin, Xue; Yang, Fang; Zhang, Li-Guo; Liu, Tong-Gang; Fu, Yu-Fei
Abstract: Purpose: To explore the clinical efficacy and long-term outcomes of accessory hepatic vein (AHV) recanalization as a means of treating hepatic vein (HV)-type Budd–Chiari syndrome (BCS). Methods: Between January 2011 and December 2018, a total of 46 symptomatic HV-type BCS patients were treated by AHV recanalization in our hospital. The technical and clinical success of this treatment, as well as associated long-term patient prognosis was assessed herein. Results: The AHV recanalization approach was technically successful in 100% of patients, without any instances of complications associated with the operation. This procedure was 95.7% (44/46) clinically successful and resultant. AHV re-obstruction occurred in 12 patients. The cumulative primary one-, two-, and five-year patency rates were 77.3%, 71.7%, and 71.7%, respectively. The secondary cumulative one-, two-, and five-year patency rates were 97.7, 87.1, and 87.1%, respectively. The five-year patency rates did not differ significantly between patients treated with balloons and stents ( p   =  .674). Based on Cox-regression analysis, younger age was an independent predictor of re-obstruction ( p  = .005). The cumulative one-, two-, and five-year survival rates were 97.7, 92.2, and 92.2%, respectively. Conclusions: AHV recanalization is a safe and effective treatment for HV-type BCS.